2018
DOI: 10.1101/365460
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FAM35A co-operates with REV7 to coordinate DNA double-strand break repair pathway choice

Abstract: # contributed equally to the work Running title: FAM35A is a novel DNA repair factor.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
108
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(115 citation statements)
references
References 68 publications
7
108
0
Order By: Relevance
“…Although structural information on the SHLD2 OB‐folds is currently unavailable, the purified SHLD2 C‐terminus binds to DNA, with a strong preference for ssDNA that is consistent with the binding properties of other OB‐fold proteins . ssDNA binding in vitro is abolished by the same aromatic residue mutations that disable the ability of SHLD2 to suppress HR, underlining ssDNA binding as a key function of SHLD2 .…”
Section: Introductionmentioning
confidence: 62%
“…Although structural information on the SHLD2 OB‐folds is currently unavailable, the purified SHLD2 C‐terminus binds to DNA, with a strong preference for ssDNA that is consistent with the binding properties of other OB‐fold proteins . ssDNA binding in vitro is abolished by the same aromatic residue mutations that disable the ability of SHLD2 to suppress HR, underlining ssDNA binding as a key function of SHLD2 .…”
Section: Introductionmentioning
confidence: 62%
“…As 53BP1 works together with the rest of its downstream cofactors to block over-resection of DNA DSBs, loss of any of these proteins partially restores RAD51 filament formation, functional HR and PARP-inhibitor resistance in BRCA1-deficient cells. Notably, whereas recruitment of RIF1, REV7 and SHLD1/2/3 depends on intact 53BP1, losing the downstream proteins does not prevent 53BP1 from forming IRIF [44][45][46][47] . Thus, in the absence of its co-factors, 53BP1 is still bound to DSB-proximal chromatin and therefore might interfere with efficient PALB2 recruitment, especially in BRCA1-deficient settings.…”
Section: Discussionmentioning
confidence: 98%
“…However, it remained elusive how the sequential recruitment of these proteins to DSBs inhibits resection because neither of them contains any clear catalytic activity. In a collective search for novel factors involved in HR regulation, several groups recently performed proteomics studies and genome-wide PARPi-resistance CRISPR/Cas9 screens and reported the identification of the Shieldin (SHLD) protein complex as an active inhibitor of resection [64][65][66][67][68][69][70] (Box 2). This complex, comprising REV7, SHLD1, SHLD2, and SHLD3, is recruited to DSBs via SHLD3 in a 53BP1-and RIF1dependent manner.…”
Section: Reactivation Of Hr As Mechanisms Of Parpi Resistancementioning
confidence: 99%